Time between recall visits and residual probing depths predict long‐term stability in patients enrolled in supportive periodontal therapy. (28th January 2019) - Ramseier, Christoph A.; Nydegger, Martina; Walter, Clemens; Fischer, Gabriel; Sculean, Anton; Lang, Niklaus P.; Salvi, Giovanni E.
Abstract: Aim: To relate the time between recall visits and residual periodontal probing depths (PPDs) to periodontal stability in patients enrolled in supportive periodontal therapy (SPT). Materials and methods: Retrospective data on residual PPDs from 11, 842 SPT visits were evaluated in SPT patients at the Medi School of Dental Hygiene (MSDH), Bern, Switzerland, 1985–2011. A residual PPD‐based algorithm was developed to compute SPT intervals with no expected change of residual PPD. Results: A total of 883 patients aged 43.9 (±13.0) years and 55.4% ( n  =   489) being females were identified. Linear mixed model analysis yielded highest statistically significant impact on PPD change with time between SPT visits, presence of residual PPD ≥4 mm, and bleeding on probing ( p  <   0.0001). Patients returning for SPT five times consecutively earlier than computed presented mean % PPDs ≥4 mm of 5.8% (±3.9) compared with patients returning later (19.2%, ±7.6) ( p  <   0.0001). Additionally, patients attending >50% of their SPT visits earlier versus later demonstrated increased periodontal stability after 5 years ( p  =   0.0002) and a reduced frequency of tooth loss (0.60, ±0.93 versus 1.45, ±2.07) after 20 years ( p  <   0.0001). Conclusions: To reach and maintain periodontal stability during SPT, individual quantitative data from comprehensive residual PPD profiles may contribute to the improved planning of SPT intervals.